2002
DOI: 10.1099/0022-1317-51-4-344
|View full text |Cite
|
Sign up to set email alerts
|

Mixed species biofilms of Candida albicans and Staphylococcus epidermidis

Abstract: A simple catheter disk model system was used to study the development in vitro of mixed species biofilms of Candida albicans and Staphylococcus epidermidis, two organisms commonly found in catheter-associated infections. Two strains of S. epidermidis were used: a slime-producing wild type (strain RP62A) and a slime-negative mutant (strain M7). In mixed fungal-bacterial biofilms, both staphylococcal strains showed extensive interactions with C. albicans. The susceptibility of 48-h biofilms to fluconazole, vanco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
223
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(239 citation statements)
references
References 26 publications
8
223
0
6
Order By: Relevance
“…Harriott et al reported that C. albicans induces S. aureus vancomycin resistance during multi-species biofilm formation [51]. In another study, Adam et al showed that in multi-species biofilms of C. albicans and S. epidermidis, extracellular polymer produced by S. epidermidis can inhibit penetration of antifungal drug fluconazole while C. albicans can protect the slime-negative S. epidermidis against vancomycin [52].…”
Section: Interactions In Multi-species Biofilmsmentioning
confidence: 99%
“…Harriott et al reported that C. albicans induces S. aureus vancomycin resistance during multi-species biofilm formation [51]. In another study, Adam et al showed that in multi-species biofilms of C. albicans and S. epidermidis, extracellular polymer produced by S. epidermidis can inhibit penetration of antifungal drug fluconazole while C. albicans can protect the slime-negative S. epidermidis against vancomycin [52].…”
Section: Interactions In Multi-species Biofilmsmentioning
confidence: 99%
“…Perhaps the most important bacterial-fungal interaction led to the discovery of penicillin (Fleming 1929). Physical interactions between fungi and bacteria include forming mixed biofilms with one another and the ability of bacteria to attach to fungal hyphae, inhibiting filamentation and biofilm formation (Adam et al 2002, Peleg 1066MYCOLOGIA et al 2008. Bacteria also produce antifungal molecules that affect morphology and virulence of Candida (Hogan et al 2004).…”
Section: Cross-kingdom Interactionsmentioning
confidence: 99%
“…Dual-species biofi lm formation was assessed on Foley catheter pieces 9,10 . Briefl y, discs of catheter material (surface area: 0.5cm…”
mentioning
confidence: 99%